A Dive into the Experiences on Menopause and Andropause - Carmona, Cherry Faith; Bancil, Ivan; Beberino, Maedane Loise; Nastor, Marc Ceasar; Ignacio, Darwin (Journal of Interdisciplinary Perspectives, 2025)
Menopause and andropause are significant biological transitions that individuals experience, yet they are often surrounded by misunderstanding and stigma. For women, menopause signifies the end of reproductive capability, while men typically undergo a gradual decline in reproductive function. This study sought to explore the experiences of individuals undergoing menopause and andropause, focusing on their biological, cognitive, psychological, and social experiences. The researchers employed a qualitative phenomenological research design, conducting face-to-face semi-structured interviews with twelve (12) participants: six (6) women experiencing menopause and six (6) men experiencing andropause, selected through purposive sampling. The collected data were analyzed using Braun and Clarke’s (2006) thematic analysis. The results indicated that individuals experiencing menopause and andropause encounter a range of experiences, including managing health issues, adapting to physical changes, handling personal relationships, coping with heightened emotions, and changed social dynamics. Additionally, the findings revealed the interconnectedness of biological changes, cognitive difficulties, psychological effects, and social dynamics. Recognizing these diverse experiences is essential for understanding their impact on well-being. The study's findings could serve as a foundation for developing interventions to enhance individuals' welfare and provide strategies to address these multifaceted challenges.